(untitled) (Global Journal of Human-Social Science, 2020)
The paper proposes the territory as the fourth dimension of sustainable development. Research starting from three dimensions of sustainable development -economic, social, environmental -highlights the difference between the spatial approach and the territorial approach in sustainable development practices. The paper shows that to include in the development approach the morphological (hilly, mountain, plain), functional (metropolitan or non-metropolitan city, cross border region), traditional (port city, financial city, industrial city), government (National strategy, special laws, etc.), governance (formal and not formal network, institutional/ noninstitutional body) aspects, leads to different development results than not including them. This evidence shows to distinguish development practices from sustainable development practices as emerged from recent Territorial Impact Assessment studies in which policies, through the territorialization of the results, guide planning actions: (local) planning actions selected on (general) policy objectives create the conditions for adaptation (about planning) and mitigation (about policies) of human actions on the environment, thus being able to speak of sustainable development.